ANALISIS PERSEPSI PERSONIL OPERASIONAL BANDARA TERHADAP IMPLEMENTASI SAFETY MANAGEMENT SYSTEM (SMS) DI BANDARA ADI SUMARMO SURAKARTA - , IMMADUDDIEN ABIL FADA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Adi Sumarmo Airport in Surakarta, which in the last five years has increased very significant passenger growth. In the last 5 years Adi Sumarmo Airport passenger experiencing a surge by 138%. Development of air transport in Indonesia with considerable growth, the factor of safety should be the first and should be improved. Look at the growth of passengers at the Adi Sumarmo Airport and in accordance with UU No. 1 of 2009 on âAviationâ and KM 8/2010, the airport must carry out or implement a Safety Management System (SMS) which can improve aviation safety, especially in Adi Sumarmo Airport. The intent and purpose of this research to identify the factors that influence the perception of airport operations personnel in providing an assessment of implementation of the Safety Management System (SMS), analyzing the performance of aviation safety services that had been performed by Adi Sumarmo Airports, so it can be used for our evaluation materials to achieve of aviation safety services in accordance with national and international regulations.. By looking at the above problems conducted research on perceptions of operational personnel of the SMS implementation at Adi Sumarmo Airport. The research was done by filling the Safety Management System Gap Analysis Checklist by operational managers to determine the extent of the application of SMS has been implemented, and by conducting a factor analysis of the perception of operational personnel to the implementation of SMS in the airport. SMS gap analysis of the results it can be concluded that the position of SMS implementation in Adi Sumarmo Airport based on the stage implementation of SMS in the Safety Management Manual Doc. 9859, 2009 that are in Phase I - Planning Implementation of Safety Management System (SMS). While the results of factor analysis on the perception of operational personnel shows lifeware factor (human resources) to get the lowest performance assessment. This indicated that lifeware factors need to be given more attention to get a better assessment performance. So that the performance of of aviation safety at Adi Sumarmo Airport will be better.